Réponses

2013-01-02T20:47:07+01:00

e = 9x²+12x +4 -(3x²+21x+2x+14)

= 9x²+12x+4-3x²-21x-2x-14

= 6x²-11x-10

 

factorisation

= (3x+2)(3x+2)-(x+7)

= (3x+2)(3x+2-x-7)

=(3x+2)(2x-5)

 

pour x = 1/2

E = 6*(1/2)² -11/2-10

= 6/4-22/4-40/4

= 56/4 = 14

2013-01-02T23:08:01+01:00

e = 9x²+12x +4 -(3x²+21x+2x+14)

= 9x²+12x+4-3x²-21x-2x-14

= 6x²-11x-10

 

factorisation

= (3x+2)(3x+2)-(x+7)

= (3x+2)(3x+2-x-7)

=(3x+2)(2x-5)

 

pour x = 1/2

E = 6*(1/2)² -11/2-10

= 6/4-22/4-40/4

= 56/4 = 14